Etiology, Pathogenesis, Origin and Prevention of Ventricular Arrhythmia - Turayev Hikmatillo Negmatovich (Journal of Science in Medicine and Life, 2024)
The heart is an organ that ensures the continuous movement of blood through the veins in the desired direction. It occurs due to the occurrence of impulses that stimulate the excitation and contraction of the myocardium. In a healthy person, different parts of the heart contract alternately, first the atria, and then the ventricles. The right atrium has a main source of rhythm called the sinus node. In addition to the sinus node, other areas of the myocardium can generate impulses and create a rhythm. However, in a healthy person, they do not cause arrhythmias due to the normal functioning of the sinus node.